Measuring the effectiveness of a car seat program in an urban, level one pediatric trauma center - Ross Budziszewski; Rochelle Thompson; Thomas Lucido; Janelle Walker; Loreen K. Meyer; L. Grier Arthur; Harsh Grewal (BMC, 2021)
Abstract Background Motor vehicle collisions (MVCs) are a significant safety issue in the United States. Young children are disproportionally impacted by car accidents and suffer high rates of injuries and mortality. When used properly, car seats have been found to reduce the severity of injuries. However, individuals from low-income areas often do not have access to education or car seats compared to those in suburban or higher income areas. Therefore, the goal of the present study was to measure the effectiveness of a car seat program in an urban, Level I Pediatric Trauma Center on caregiver car seat knowledge. Methods Caregivers (N = 200) attended a single, one-hour car seat educational program with a Child Passenger Safety Technician (CPST). The sessions included educational and hands-on components, where caregivers were asked to complete a seven-item pre-post knowledge assessment. For completion of the course, caregivers received a car seat for their child. Results A paired t-test revealed that the workshop significantly increased caregiver knowledge from pre-post: t (199) = − 12.56, p < .001; d = 1.27. McNemar's Chi-Square analyses displayed that caregivers increased in all knowledge categories (p < .001). Conclusions While caregivers in urban areas or in low-income areas may have less access to resources, hospital-led car seat courses can increase knowledge of proper car seat usage in these communities. These findings should be used to establish programs in hospitals in areas where these resources are not readily available to caregivers.